Defining the Balance between Regeneration and Pathological Ossification in Skeletal Muscle Following Traumatic Injury - Davies, Owen G.; Liu, Yang; Player, Darren J.; Martin, Neil R. W.; Grover, Liam M.; Lewis, Mark P. (Frontiers in Physiology, 2017)
Heterotopic ossification (HO) is characterised by the formation of bone at atypical sites. This type of ectopic bone formation is most prominent in skeletal muscle, most frequently resulting as a consequence of physical trauma and associated with aberrant tissue regeneration. The condition is debilitating, reducing a patient’s range of motion and potentially causing severe pathologies resulting from nerve and vascular compression. Despite efforts to understand the pathological processes governing HO, there remains a lack of consensus regarding the micro-environmental conditions conducive to its formation, and attempting to define the balance between muscle regeneration and pathological ossification remains complex. The development of HO is thought to be related to a complex interplay between factors released both locally and systemically in response to trauma. It develops as skeletal muscle undergoes significant repair and regeneration, and is likely to result from the misdirected differentiation of endogenous or systemically derived progenitors in response to biochemical and/or environmental cues. The process can be sequentially delineated by the presence of inflammation, tissue breakdown, adipogenesis, hypoxia, neo-vasculogenesis, chondrogenesis and ossification. However, exactly how each of these stages contributes to the formation of HO is at present not well understood. Our previous review examined the cellular contribution to HO. Therefore, the principal aim of this review will be to comprehensively outline changes in the local tissue micro-environment following trauma, and identify how these changes can alter the balance between skeletal muscle regeneration and ectopic ossification. An understanding of the mechanisms governing this condition is required for the development and advancement of HO prophylaxis and treatment, and may even hold the key to unlocking novel methods for engineering hard tissues.